Investigação da resistência bacteriana e avaliação de metodologias em isolados clínicos de Pseudomonas aeruginosa e Acinetobacter spp. de diferentes anos em um hospital universitário - Santos, Silvana Oliveira dos (2017)
Pseudomonas aeruginosa and Acinetobacter spp. are microorganisms worldwide reported as pathogens of high prevalence in the etiology of nosocomial infections; they are opportunistic and have clinical importance in Health Care Related Infections. The high resistance to antimicrobials that these species present is a major challenge in current medicine. Thus, the present work aimed to investigate bacterial resistance in isolates of P. aeruginosa and Acinetobacter spp. collected in two periods (August 2011 and January 2012 and August 2015 to January 2016) from a university hospital in southern Brazil, as well as to evaluate methodologies for the identification of resistance to meropenem in isolates from the 2011/2012 collection and to identify the resistance to colistin in the isolates of the 2015/2016 collection. In this study, 63 isolates of P. aeruginosa and 39 of Acinetobacter spp. (2011/2012), as well as 231 of P. aeruginosa and 62 of Acinetobacter spp. (2015/2016) of several clinical specimens from the University Hospital of Santa Maria, Rio Grande do Sul. Analyzes of antimicrobial resistance profiles in all clinical isolates from the years 2011/2012 and 2015/2016 and the investigation of resistance to colistin in the isolates of the 2015/2016 collection were carried out by the antimicrobial susceptibility test in VITEK®2-bioMérieux automated system. The disc diffusion methodologies and the automated MicroScan®-SIEMENS and VITEK®2-bioMérieux were evaluated statistically when comparing the methodology of microdilution in broth, a technique considered standard for the identification of resistance to carbapenem meropenem. In the evaluation of the profile of the isolates, a reduction in resistance to imipenem and meropenem in P. aeruginosa was detected from 64.10% to 53.24%, from 2011/2012 to 2015/2016. In Acinetobacter spp. this decrease was also observed, from 88.57% to 74.19% between the two periods. Concerning the evaluation of the methodologies for the identification of resistance to carbapenem meropenem in the 2011/2012 isolates, the diffusion of the disc presented 91% of sensitivity, 77% of specificity and 86% of accuracy, demonstrating good agreement with the standard method (Kappa K)= 0.688), while the automated methodology MicroScan®-SIEMENS presented 100%, 77% and 92%, respectively for the same previous items and the agreement was higher (K= 0.820 - excellent agreement). The VITEK®2-bioMérieux automated methodology was 97%, 55% specificity and 82% accuracy, and the index was considered regular (K = 0.577). The resistance to colistin in the isolates of 2015/2016 was identified in nine strains of P. aeruginosa (9/231-3,89%) and none Acinetobacter spp.. From the resistance profile of the evaluated isolates, it can be concluded that P. aeruginosa and Acinetobacter spp. from 2015/2016 were more sensitive against the great majority of antimicrobials tested, however, the presence of resistance to colistin in these strains, a fact that is shocking because this antimicrobial is the main therapeutic option for the treatment of multiresistant bacteria. The data from this study allow us to recommend the association of methodologies for the correct identification of resistance to carbapenem meropenem. In this study, disk diffusion and MicroScan®-SIEMENS proved to be good methodologies to identify this type of resistance. In addition, the results show the need for continuous monitoring of P. aeruginosa and Acinetobacter spp. to minimize the multidrug resistance in these isolates and to evaluate the local resistance pattern.